Pengaruh Strategi Everyone Is A Teacher Here terhadap Motivasi Belajar Siswa - Grandi Impati; Jamila Jamila (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
The problem of this research is There Is Influence Everyone Is A Teacher Here Strategy on Student Motivation Class XI In SMK Muhammadiyah 04 Medan T.P 2016/2017. The purpose of this study is to determine the effect of Everyone Is A Teacher Here Strategy on Student Motivation Class XI In SMK Muhammadiyah 04 Medan TP 2016/2017 which amounted to 211 Students consisting of 6 classes and divided into 3 departments and the sample studied is class XI AK 2 SMK Muhammadiyah 04 Medan as many as 38 students. Instrument used is questionnaire and test. Which questionnaire is doing observations in SMK Muhammadiyah 04 Medan to know the motivation of student learning. The method used in this research is quantitative method with product moment analysis unit. From the results of this study can be seen improving student learning motivation by using the influence of Everyone Is A Teacher Here strategy on the subject of Citizenship Education with research conducted, it was found that Everyone Is A Teacher Here learning affects the motivation of student learning on the subject of Citizenship Education. From the results of the hypothesis calculation obtained tcount = 2.309 for the significant level α = 0.05 and dk = n-2 = 38-2 = 36, then obtained the price r table = 1.6892. Obtained tcount 2.309> ttabel 1.6892, this means Ha accepted means a significant influence between strategy Everyone Is A Teacher Here on student learning motivation.